Geochemical exploration in tropical terrains with special reference to base metals - Chiconela, Domingos Rubão (Rhodes University, Faculty of Science, Department of Geology, 1996)
In tropical areas, the high rainfall induces severe-and pervasive weathering, producing a thick soil cover. The lithologies underneath may b~ recognised using geochemical mapping, which is based on certain elements that have the ability to differentiate between various lithologic units. Elements that are independent of the weathering process are normally selected for this purpose. The chemistry of mobility of base metals is an important factor to take into account when evaluating the mobility and distribution of these elements in a soil profile. Factors such as pH, Eh, organic material, clay minerals, Fe and Mn oxides are normally key aspects to be considered. When iron-rich rocks undergo deep weathering, lateritic profiles are developed. These are widespread in a belt bordering the equatorial zone, including the Brazilian shield, West and East Africa, parts of India and Northern Australia. In these profiles, the high rainfall promotes intense leaching of the different horizons. Where the pre-existing profiles are mostly preserved, the base metals are distributed throughout the profile: in the upper ferruginous horizon, goethite and hematite can adsorb large amounts of Mo, resulting in large dispersion halo. Other base metals such as Cu and Zn are less resistant in these freely-drained profiles and, therefore, they may be partly leached from the profile. In the lower horizons, Cu, ,zn, Ni and Co are retained, hosted in kaolinite and smectite, and thus, a high geochemical contrast will be identified in this horizon at the expense of a decline in the size of the dispersion haloes. The pre-existing profiles can be truncated, with a thin stone line developing at the contact between the lateritic profile and the recent soil. The conditions in these environments favour the retention of most of the pathfinder and target elements in all soil horizons, with the B horizon showing the highest contrast. If the primary rock is rich in AI, a bauxitic profile will be developed. The world distribution of bauxites closely resembles that of laterites. The behaviour of Co and Ni is very similar to that of iron during the bauxitization. Furthermore, the factors that induce residual enrichment of Al with removal of Fe in the soil profile will cause significant depletion of Co and Ni in these profiles. These metals are then concentrated at the base of the profile because of precipitation from downward percolating solutions. Many karst bauxite deposits in Southern Europe are enriched with Ni and Co in the basal horizon. Such horizon is mined as nickel ore in the bauxites of the Lokris region in Greece. Copper and molybdenum are strongly enriched.in bauxitic profiles. Concentration ratios are 8 and 3.2 for Cu and Mo respectively. Molybdenum is closely related to goethite and hematite, and therefore, the high concentration of Mo in a bauxitic profile will be consistent with the horizon where iron is concentrated. Copper concentrates at the base of the iron rich-horizon but also appears enriched in the saprolite together with Co. When sulphide bodies occur, in this environment, deep and penetrative weathering has resulted in considerable near-surface mobilization of iron and silica. The supergene alteration commonly obscures the identity of the primary sulphides at the surface. In this case, geochemical assessment of the resulting gossan has proved to be crucial in mineral exploration. A search in the secondary mineral assemblage, volatile and precious metals may lead to the information on the composition of the primary sulphide assemblage. The conclusion that will be reached is that if the geochemical properties (mobility, affinities with Fe or Mn oxides and/or clay minerals) of each of the base metals are understood, an appropriate sampling (optimum size-depth combination) will then be done. In such cases, a subdued, weak, but significant, geochemical response will be identified in the surface horizon.
Keywords: Geochemical prospecting -- Research -- Tropics; Geological mapping -- Research -- Tropics; Weathering -- Research -- Tropics; Geochemistry -- Research